2018
DOI: 10.15392/bjrs.v6i1.333
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and trends of Computed Tomography usage among pediatric and young adult patients in a private hospital in Rio de Janeiro, 2005-2015

Abstract: Computed tomography (CT) scanning is a relatively high-dose procedure which use has been rapidly increasing in many countries, although a decline has been observed recently in some developed countries. Relatively little is known about CT usage in Brazil. A recent report showed that number of CT procedures among outpatients of the Brazilian public healthcare system (SUS) tripled from 2001 to 2011 and about 13% of all CTs procedures were performed in pediatric and young adult patients. In the present study, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(51 reference statements)
0
3
0
Order By: Relevance
“… 2 Even with this knowledge, the total number of yearly CT examinations grows. 3 , 4 Large‐scale studies have indicated the detrimental impact of ionizing radiation on human tissue, with the increased radiosensitivity of pediatric populations compared to adult populations, an area of particular concern. 5 During a child's development, cells proliferate more rapidly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 Even with this knowledge, the total number of yearly CT examinations grows. 3 , 4 Large‐scale studies have indicated the detrimental impact of ionizing radiation on human tissue, with the increased radiosensitivity of pediatric populations compared to adult populations, an area of particular concern. 5 During a child's development, cells proliferate more rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, CT radiation doses account for over half the population effective dose received from medical sources 2 . Even with this knowledge, the total number of yearly CT examinations grows 3,4 . Large‐scale studies have indicated the detrimental impact of ionizing radiation on human tissue, with the increased radiosensitivity of pediatric populations compared to adult populations, an area of particular concern 5 .…”
Section: Introductionmentioning
confidence: 99%
“…• 2020 3 -the public healthcare system of Brazil [28] -between 2008 and 2011, when CT usage increased by 13% per year. Another study [29], focused on CT procedures in a single private general hospital in the city of Rio de Janeiro, reported that patients below 20 years of age underwent around 8% of all CT examinations performed between 2005 and 2015, with an annual increasing rate of 10%.…”
Section: Introductionmentioning
confidence: 99%